The Ethical and Unethical Behaviors That Women Volleyball Players Observed on Their Coaches - Esra Ünal, Abdülkerim Çeviker (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study; It was conducted to determine the level of compliance of their trainers with professional ethical and unethical behaviors by evaluating the licensed and licensed female volleyball players in the 2019-2020 season within the body of the Turkish Volleyball Federation. Methods: The universe of our study consists of 960 female athletes in the TVF Women’s 2nd League. The sample of our study consisted of 287 female athletes who participated in our study on a voluntary basis. In our study, the measurement tool "The level of compliance of the coaches with the professional ethics of coaching" developed by (Özbek, 2019) was used. In addition, a personal information form for the athletes was also applied. The obtained data were analyzed by the SPSS 27.0 package program. Since the data did not meet the normal distribution condition, the comparison of two independent groups was made with the Mann Whitney U test, and the independent multiple group comparisons were made with the Kruskal Wallis tests. Correlation analysis was used to determine the direction and degree of the relationship between the sub-dimensions of the scale. Results and Conclusion: As a result, it is seen that there is a significant difference between the sub-dimensions of the views of the athletes about the coaching profession ethics. It has been concluded that there is a significant difference in their opinions regarding the level of compliance with the professional ethics of coaching according to the variable of age, marital status, and the year of doing sports. It has been concluded that there is a significant difference in terms of professionalism, respect, responsibility, tolerance and scale in terms of the level of compliance with the professional ethics of coaching of the athletes about their coaches (p>0.05). The marital status, department graduated, income level, age and sports of the athletes. It is seen that there is a significant difference between the year of construction variables (p <0.05).